The prevalence of short stature among school children and adolescents in Tripoli, Libya in 2009-2010 - Ramadan, Mabruka; Khashebi, Rowida; Rajab, Faten (Ibnosina Journal of Medicine and Biomedical Sciences, 2021)
Background: Short stature has an impact on children's physical and mental health. Data on the prevalence of short stature in Libyan children are limited. Objectives: We aimed to ascertain the prevalence of short stature among school children in Tripoli, Libya. Patients and Methods: In this cross-sectional study, we included 419 school children (235 boys and184 girls) selected from different primary and preparatory schools in the City of Tripoli. The study was conducted between April 2009 and October 2010. Trained pediatricians took their anthropometric measurements (i.e., height and weight). The WHO-2007 Z-score charts and UK-WHO growth charts were used to calculate the prevalence of short stature (defined as standard deviation score of height <2 in same gender and age). Results: The overall prevalence of short stature using WHO-2007 Z-score and UK-WHO growth charts were 5.0% and 5.7%, respectively. (4.3% was moderate and 0.7% was severe). Boys and girls had no significant difference in the prevalence of short stature using 2007 WHO reference data (5.5% vs. 4.3%; P = 0.656). Similarly, there was no difference between the prevalence of short stature between boys and girls when applying UK-WHO growth charts (6.8% vs. 4.3%; P = 0.3). There is a statistically significant relationship between the prevalence of short stature (increase) and students' increasing age. Conclusions: Short stature is not an uncommon problem in children; they need early assessment because intervention time is crucial in this condition.
Keywords: Anthropometric measurements; growth; Libya; schoolchildren; short stature; Tripoli